2015
DOI: 10.32398/cjhp.v13i1.1811
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Demographic and Substance Use Correlates of Hookah Use in a Sample of Southern California Community College Students

Abstract: Background and Purpose Hookah smoking is a growing young adult phenomenon, particularly among college students. Many users feel that it is safer than other tobacco products, although its health threats are well documented. Little is known about hookah use rates in community colleges that are attended by nearly half of all US college students. This study examined hookah use in a diverse convenience sample of students attending two southern California community colleges. Methods In fall 2011, a cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Jamil, Elsouhag, Hiller, Arnetz, and Arnetz (2010) administered a survey on hookah smoking behavior to a sample of US adults and found that 95% of respondents reported smoking hookah as a means of “socialize with family/friends,” and with therefore may be common among college students, as prior studies have found (e.g., Goodwin et al 2014). Prior studies have found high levels of hookah use among students pursuing advanced degrees, such as medical degrees (Almerie et al, 2008; Jawad et al, 2013), and among college students (Chen & Loukas, 2015; Montgomery et al, 2015). Therefore, it is not surprising being a student is associated with increased levels of use among this young sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jamil, Elsouhag, Hiller, Arnetz, and Arnetz (2010) administered a survey on hookah smoking behavior to a sample of US adults and found that 95% of respondents reported smoking hookah as a means of “socialize with family/friends,” and with therefore may be common among college students, as prior studies have found (e.g., Goodwin et al 2014). Prior studies have found high levels of hookah use among students pursuing advanced degrees, such as medical degrees (Almerie et al, 2008; Jawad et al, 2013), and among college students (Chen & Loukas, 2015; Montgomery et al, 2015). Therefore, it is not surprising being a student is associated with increased levels of use among this young sample.…”
Section: Discussionmentioning
confidence: 99%
“…What is known about the correlates of hookah use come mainly from convenience samples (Daniels & Roman, 2013; Jarrett, Blosnich, Tworek, & Horn, 2012; Linde et al, 2015; Smith et al, 2011) or representative samples of adolescents (Amrock, Gordon, Zelikoff, & Weitzman, 2014), high school students (Palamar et al, 2014), and college students (Chen & Loukas, 2015; Montgomery et al, 2015). However, findings from these studies cannot be generalized to the overall adult population – additionally because a large minority of US high school students fail to complete high school, and of those who receive a high school degree, a smaller percentage enroll in university and earn a college degree (Chapman, Laird, Ifill, & KewalRamani, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, all participants reported recent cigarette smoking; while hookah users are more likely to use cigarettes and other products (Grinberg & Goodwin, in press; Montgomery et al, 2015; Shephardson & Hustand, 2016), some do not. Additionally, the sample included relatively few African Americans, whom initial evidence suggests may use hookah at lower rates than other groups (Jones & Cunningham-Williams, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, many young adults perceive hookah as less harmful, less addictive, and more socially acceptable than cigarettes (Berg et al, 2015; Heinz et al, 2013). These perceptions increase risk of use (Montgomery et al, 2015). …”
mentioning
confidence: 99%
“…Rates of nonwhite students and students with low socioeconomic status (SES) are higher in community colleges compared to traditional colleges and universities [1-3]. Of all college students, nearly half (42-45%) attend community colleges [4,5].…”
Section: Introductionmentioning
confidence: 99%